Yogākṣara Dalam Śiwa Tattwa Sebagai Laku Spiritual Untuk Mencapai Kalepasan - Ariasa Giri, I Made; Windya, Ida Made (Jurnal Penelitian Agama Hindu, 2024)
Tattwa texts in Bali contain Śiva’s philosophy such as Wṛhaspati Tattwa, Jñānasiddhanta, Jñāna Tattwa, Gaṇapati Tattwa, Sanghyang Mahājñana, Catur Prenawa and Tutur Amertha Kundalini Lontar Śiwa Tattwa contains Śiwa's teachings about divinity, creation and liberation. The interesting in Śiwa Tattwa is the teaching of kalêpasan with the Sadanggayoga concept through ākṣara practice known as yogākṣara. The yogākṣara system as a religious system in Bali has never been studied seriously based on academic methods. Therefore, it needs attention to carry out a more in-depth study. This research aims to interpret yogākṣara in the Śiwa Tattwa to achieve liberation. The method used in this research is a qualitative method with a descriptive interpretive approach. The primary data in this research is the Śiwa Tattwa text. Secondary data is obtained from literature in the form of books and research results relevant to the research topic. Data collection used observation, interview, documentation, and literature study techniques in this research. Semiotic theory and religious theory are used in this research. The results of this research that the yoga structure contained in Śiwa Tattwa is Sadanggayoga. The form of yogākṣara in the Śiwa Tattwa is by carrying out Panglukuan Ākṣara. Yogākṣara is also an effort to understand the nature of being oneself and achieve Śiwa consciousness. There are seven levels of consciousness dimensions in Śiwa Tattwa called Sapta Pada. From the results of this research, it can be concluded that yogāksara is a spiritual practice to achieve Śiwa consciousness, namely achieving kalêpasan (liberation).